Prevalence of headache in an elderly population: attack frequency, disability, and use of medication. Issue 3 (1st March 2001) - Prencipe, M; Casini, A R; Ferretti, C; Santini, M; Pezzella, F; Scaldaferri, N; Culasso, F
Abstract : OBJECTIVES: To assess the 1 year prevalence of tension-type headache (TTH), migraine headache (MH), and chronic daily headache (CDH), as well as of headache in general in a rural elderly population. METHODS: A door to door two phase survey was carried out on all elderly (⩾65 years) residents in three villages in central Italy. Participants completed a standardised headache questionnaire and underwent a clinical evaluation by a neurologist. Headache diagnosis was made according to the classification of the International Headache Society, with minor modifications for the classification of patients with MH with⩾15 attacks/month. RESULTS: Eight hundred and thirty three (72.6%) of the 1147 eligible persons completed the study protocol. One year prevalence rates were respectively 44.5% for TTH, 11.0% for MH, 2.2% for symptomatic headaches, and 0.7% for the remaining types of headache. The prevalence of headache in general was 51.0% because 62 residents had both TTH and MH attacks. Prevalence rates of patients with headache were higher in women than men (62.1% and 36.6% respectively) and decreased steadily with age for the 65–74, 75–84, and 85–96 age groups (56.7%, 45.2% and 26.1% respectively). Prevalence rates were 20.4% for patients with moderate to severe attacks, 18.0% for those with ⩾1 attacks a month, and 4.4% for those with CDH. Of the 425 with headache 52 (12.2%) had not taken any drugs for their attacks in the previous year, 195 (45.9%) had taken them regularly, and 178 (41.9%) had taken them only when the headache pain interfered with activities that could not be postponed. Medication overuse was reported by 37.8% of patients with CDH with higher proportions for transformed migraine than for patients with chronic TTH (69.2% and 23.8% respectively, p=0.009) CONCLUSIONS: A consistent proportion of elderly people have primary headaches and consultation with a specialist is particularly recommended for patients with moderate or severe attacks, or with CDH.